The research on European pond turtle within the special nature reserve "Ludaš Lake" - Golubović, Ana; Maričić, Marko; Bjelica, Vukašin; Grabovac, David; Popović, Miloš (Zaštita prirode (Online), 2022)
According to international and national legislation European pond turtle and its habitats have been highlighted as priority regarding protection. Due to such status, this species is the subject of population research and active protection throughout its native range, however, systematic research was started only recently on the territory of the Republic of Serbia. Population studies of pond turtles have lasted the longest in our country at Lake Ludaš, where the twelfth research season was marked in August 2022. This paper presents the population parameters processed so far, including: population density, survival rate, gender ratio of adult individuals, as well as gender dimorphism in shell size and body mass. In addition, the threatening factors that were recorded on the terrain, as well as active protection measures that were undertaken or proposed have been described.